Foreign market entry strategy : the Case Study of Kazakhstan and Russia - Maksimenko, Elena (2018)
Diploma thesis examines the topic of entry to a new market. The fundamental topic is European company entry to the emerging market. Diploma thesis is divided to literature analysis, practical study of the diploma thesis itself and summary of diploma thesis.The main objective of the diploma thesis is to develop the strategy of entry, of IT companies, to the Russian and Kazakh markets. The hypothesis is the following statement: the entry on Kazakh market is linked with a bigger number of bureaucratic obstacles, than on the Russian. The diploma thesis uses following methods: literature analysis, analysis of statistical data, analysis of basic economic and demographic situation, comparison and analogy. Research is based on Russian, Kazakh and other recourses of information.